2012
DOI: 10.1186/1471-2164-13-614
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles salivary gland proteomes from major malaria vectors

Abstract: BackgroundAntibody responses against Anopheles salivary proteins can indicate individual exposure to bites of malaria vectors. The extent to which these salivary proteins are species-specific is not entirely resolved. Thus, a better knowledge of the diversity among salivary protein repertoires from various malaria vector species is necessary to select relevant genus-, subgenus- and/or species-specific salivary antigens. Such antigens could be used for quantitative (mosquito density) and qualitative (mosquito s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 93 publications
(132 reference statements)
0
21
0
2
Order By: Relevance
“…The IgG response increases signifi cantly with the increase in Anopheles exposure, as evaluated using conventional entomological methods during the transmission season (10) . The results of a study conducted by Fontaine et al also demonstrated a positive correlation between the average IgG response to SGEs of Aedes caspius and Aedes caspius density, which was affected by changes in the season and the ecological environment (18) . The level of the IgG response increased signifi cantly during peak exposure to Ae.…”
Section: Immunogenic Proteins Found In Anopheles Sundaicus Salivary Gmentioning
confidence: 82%
See 2 more Smart Citations
“…The IgG response increases signifi cantly with the increase in Anopheles exposure, as evaluated using conventional entomological methods during the transmission season (10) . The results of a study conducted by Fontaine et al also demonstrated a positive correlation between the average IgG response to SGEs of Aedes caspius and Aedes caspius density, which was affected by changes in the season and the ecological environment (18) . The level of the IgG response increased signifi cantly during peak exposure to Ae.…”
Section: Immunogenic Proteins Found In Anopheles Sundaicus Salivary Gmentioning
confidence: 82%
“…This result may be explained by the presence of several proteins in the salivary glands of Anopheles that are conserved at the genus level (7) . Some proteins families are found in all Anopheles species; these are called genus-specifi c anopheline secreted proteins and include apyrase/5′ nucleotidase, antigen 5/gvag, GE-rich/30kDa, long and short form D7, mucin/13.5kDa, SG3, SG7, SG10, and hypothetical 6.2-kDa protein families (18) . Potential proteins having molecular weights of 61-63kDa include apyrase/5′ nucleotidase, which is involved in the blood feeding process through degradation (hydrolysis) of adenosine diphosphate (ADP) and adenosine triphosphate (ATP) to adenosine monophosphate (AMP), a mediator of platelet aggregation, infl ammation, and neutrophil activation (5) (22 (23) .…”
Section: Immunogenic Proteins Found In Anopheles Sundaicus Salivary Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest here, Anopheles antigens are known humoral immune targets; antibody titers against mosquito salivary gland extracts are even indicative of mosquito biting intensity (18). Constituent salivary gland proteins are increasingly well identified (19), and some proteins, such as salivary gland protein-4 and -5, are known antibody targets (20). Aside from humoral immunity, A. stephensi bites also activate mast cells and contribute to T cell hyperplasia in lymph nodes (21).…”
mentioning
confidence: 99%
“…gambiae genome sequence in 2002 an abundance of proteomic, transcriptomic and genome wide association data have been produced to try to understand the intimate relationships between the mosquito and Plasmodium parasites with the aim of identifying rational new means to control malaria transmission [1][2][3][4][5] . Other features of Anopheles biology relevant to disease transmission have also been intensively studied, including mating behaviour, sex determination, olfactory response and insecticide resistance [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%